(untitled) (Research, Society and Development, 2020)
Objective: To analyze the degree of knowledge of nursing students about the recommendations for the prevention and treatment of pressure injuries in critically ill patients. Methodology: Descriptive, exploratory study with a quantitative approach, carried out in the first semester of 2019. The research was carried out with 70 students from the 7th, 8th, 9th and 10th semester of the undergraduate nursing course. Data were collected using a validated instrument. The research was submitted to the Research Ethics Committee (CEP) of the Undergraduate Nursing Course at the University of the Amazon (UNAMA), CAAE: 06941519.9.0000.5173. Results: There was a predominance of the female population, aged between 20 and 29 years, born in Belém and with a single marital status. It was possible to verify that most of the participants who obtained updates about the pressure injury in classes at college. One should always seek improvement in courses, lectures, articles, among other forms of improvement, aiming to always keep up to date, in face of such an important issue in the nurse’s journey, as it is considered the main piece in this care. Conclusion: To advance knowledge about PPL, it is necessary to disseminate guidelines for its prevention and treatment. There is a lack of knowledge about the prevention of pressure injuries among those surveyed, making continuous training mandatory even starting during graduation.